The Color of money [videorecording (DVD)] - Scorsese, Martin; Newman, Paul, 1925-2008; Cruise, Tom, 1962-; Mastrantonio, Mary Elizabeth (Touchstone Home Video : Dist. by Buena Vista Home Entertainment, 1999)
Aging pool shark who believes "money won is twice as sweet as money earned", forms a profitable yet volatile partnership with a young pool hustler.